25 Rituximab in patients with acute st-elevation myocardial infarction (RITA-MI). (17th July 2020) - Zhao, Tian; Mallat, Ziad; Hoole, Stephen; Aetesam-Ur-Rahman, Muhammad; Victor, Saji; Fielding, Sarah; Sage, Andy
Abstract : Background: In pre-clinical models of acute myocardial infarction (MI), mature B cells selectively mobilise inflammatory monocytes into the heart, leading to increased infarct size and deterioration of myocardial function. Anti-CD20 antibody mediated depletion of B cells limited infarct size and improved cardiac function. Rituximab is a monoclonal antibody targeted against human B cells and has been used in the treatment of certain autoimmune diseases and cancers. However, its use in cardiovascular disease is untested and is currently contraindicated. Therefore, we assessed the safety, feasibility and pharmacodynamic effect of rituximab given acutely to patients with ST elevation MI (STEMI). Method: RITA-MI was a prospective, open-label, dose-escalation, single-arm, phase 1/2a clinical trial, which tested rituximab administered as a single intravenous dose in patients with STEMI within 48hours of symptom onset. Four escalating doses (200, 500, 700 and 1000mg) were used with 6 patients in each group. Follow-up was performed during initial inpatient stay; on days 6 and 14; and at 3 and 6 months. The primary endpoint was safety, whilst secondary endpoints were changes in circulating B cells and their subsets, immune cell subsets, and cardiac and inflammatory biomarkers. [NCT:03072199] Results: Overall, rituximab was well tolerated across all doses with the most common adverse event being gastrointestinal disturbance (Table 1 ). This was due to the concomitant oral secondary prevention medication started after a STEMI. Five severe adverse events were reported, none of which were assessed as being related to the rituximab infusion. Rituximab caused near complete depletion of B cell numbers within 30 mins of starting the infusion, with the mean % depletion across all dose groups being 96.3% (95% CI 93.8-98.8%). At 6 hours a rebound in B cells was seen in the 200, 500 and 700mg dose likely related to emigration of B cells from secondary lymphoid tissues. Maximal B cell depletion was seen at day 6 which was significantly lower than baseline for all doses (p<0.001) (figure 1 A and B ). The extent of B cell repopulation at 6months was dose dependent. In addition, there was modulation of returning B cell subsets characterised by increased transitional B cells (figure 1C ). Immunoglobulin (IgG, IgM and IgA) levels were not affected during the 6months of follow-up. Rituximab also caused an acute and transient decrease in lymphocytes (both CD4+ and CD8+ T cells) and monocytes, whilst transiently increasing neutrophils at the 6 hour timepoint (figure 2 ). Cardiac biomarkers showed a decrease in CRP and BNP. Clinical echocardiogram (on 12/24 patients) showed an increase in ejection fraction at follow up (mean increase in EF of 7.8% (95% CI 3.11-12.6)). Conclusion: Rituximab appears safe and feasible when given in the acute STEMI setting. We have shown, for the first time, the acute (within 30mins) depletion of B cells with rituximab which demonstrates the biological plausibility of our treatment paradigm, In addition, we have offered new insight into the mechanism of action of rituximab. This has led directly to the setting up of a phase 2b trial. Conflict of Interest: None